Environmental Stressors on Skin Aging. Mechanistic Insights - Concepcion Parrado; Sivia Mercado-Saenz; Azahara Perez-Davo; Yolanda Gilaberte; Salvador Gonzalez; Angeles Juarranz (Frontiers Media S.A., 2019)
The skin is the main barrier that protects us against environmental stressors (physical, chemical, and biological). These stressors, combined with internal factors, are responsible for cutaneous aging. Furthermore, they negatively affect the skin and increase the risk of cutaneous diseases, particularly skin cancer. This review addresses the impact of environmental stressors on skin aging, especially those related to general and specific external factors (lifestyle, occupation, pollutants, and light exposure). More specifically, we have evaluated ambient air pollution, household air pollutants from non-combustion sources, and exposure to light (ultraviolet radiation and blue and red light). We approach the molecular pathways involved in skin aging and pathology as a result of exposure to these external environmental stressors. Finally, we reflect on how components of environmental stress can interact with ultraviolet radiation to cause cell damage and the critical importance of knowing the mechanisms to develop new therapies to maintain the skin without damage in old age and to repair its diseases.